Reconfigurable Articulated Robot Using Android Mobile Device - A.H. Rajpar; Ahmad. E. Eladwi; Imran Ali; Mohamed Bashir Ali Bashir (Journal of Robotics)
This paper focuses on the design and development of a reconfigurable three-degree-of-freedom articulated robot for conducting pick-and-place tasks. To implement the system, an Android platform for the manual control of an articulated robot using wireless Bluetooth technology was developed. This application allows the user to manually reconfigure the robot following the requirements of the integrated system via a user-friendly display. The articulated robot comprises four motors, three of which are used for positioning and orientation and finally used to carry out the pick-and-place task. An Arduino Un R3 board is used to control the movement of the links via a pulse width modulation method. We introduce a set of conveniently composed kinematic and dynamic mathematical models for positioning the robot’s arms and, in our results and discussion section, calculate and report the torque required to move each joint.